Legal Systems and Sources of Law of Armenia and Armenian Kingdom of Cilicia - Vagharshyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2016)
The developing legal system of Armenia underwent significant changes in X-XIV centuries. While being medieval, feudal and customary legal system, it transferred from unwritten to written customary law, without changing religiuos character. However, since the XIII century the political environement of Armenian legal system became negative. In addition, the changes in demographics divided the legal system in Armenia on the basis of ethno-religious feautures – Armenian and Muslim. Compared to Armenia, both the regulatory basics and the organizational and ideological elements of the legal system of the Armenian Kingdom of Cilicia were developed enough. The political factor, along with the economic and social ones stimulated the development of the legal system. This proves the rule that the Armenian law manifested progressive, humanitarian trends of development, new codifications during the periods of political independence, peace and socio-economic stability of the society.